(3GKQ HQfGeL JOQjHj ebJQM HGSJNOGe GdGdYGH GdUZjQI Ydi JfejI GdUaGJ GdHOfjI h GdGOGA GdegGQj dOi dGYHj cQI GdjO GTHGd (B(12 - 15 (3SfI (B) : (3OQGSI ejOGfjI dGMOi GdaQb GdeOQSjI dhdGjI GdJHSI s - (3bQGO, YHO GdeGdcs; (3dYLGd, jMjs; (3eYgO GdJQHjI GdHOfjI h GdQjGVjI, LGeYI GdLRGFQ (B3 s ((3GdLRGFQ s, 2021)
(3gOaJ GdOQGSI Gdi eYQaI CKQ HQfGeL JOQjHj ebJQM HGSJNOGe GdCdYGH GdUZjQI Ydi JfejI GdUaGJ GdHOfjI hGdCOGA GdegGQj dOi dGYHj cQI GdjO CTHGd, ef CLd GdGLGHI Ydi GdETcGd GdQFjSj GdeWQhM hGdeJeKd aj(B: (3gd jDKQ GdHQfGeL GdJOQjHj GdebJQM HGSJNOGe GdCdYGH GdUZjQI Ydi JfejI GdUaGJ GdHOfjI hGdCOGA GdegGQj dOi dGYHj cQI GdjO CTHGd?, hGdPj HOhQg JaQYJ efg YOI JSGDdGJ aQYjI efgG(B: 1- (3gd jDKQ GdHQfGeL GdJOQjHj GdebJQM HGSJNOGe GdCdYGH GdUZjQI Ydi JfejI GdUaGJ GdHOfjI ddGYHj cQI GdjO CTHGd? (B2- (3gd jDKQ GdHQfGeL GdebJQM HGSJNOGe GdCdYGH GdUZjQI Ydi JfejI GdCOGA GdegGQj ddGYHj cQI GdjO CTHGd? (B3- (3gd JhLO YdGbI GQJHGWjg Hjf GdUaGJ GdHOfjI hGdCOGA GdegGQj ddGYHj cQI GdjO CTHGd? hddELGHI Ydi gPg GdJSGDdGJ GaJQVfG YOI aQVjGJ efgG aQVjI YGeI JeKdJ aj(B: (3GdHQfGeL GdJOQjHj GdebJQM HGSJNOGe GdGdYGH GdUZjQI jDKQ GjLGHjG Ydi JfejI GdUaGJ GdHOfjI hGdCOGA GdegGQj ddGYHj cQI GdjO CTHGd, hGdJj HOhQgG JaQYJ efgG YOI aQVjGJ LRFjI cGfJ ceGjdj(B: 1- (3jDKQ GdHQfGeL GdJOQjHj GdebJQM HGSJNOGe GdCdYGH GdUZjQI Ydi JfejI GdUaGJ GdHOfjI ddGYHj cQI GdjO CTHGd (B2- (3jDKQ GdHQfGeL GdJOQjHj GdebJQM HGSJNOGe GdCdYGH GdUZjQI Ydi JfejI GdCOGA GdegGQj ddGYHj cQI GdjO CTHGd (B3- (3JhLO YdGbI GQJHGWjg Hjf GdUaGJ GdHOfjI hGdCOGA GdegGQj ddGYHj cQI GdjO CTHGd HYO GdOQGSI GdfXQjI hGdJj JeKdJ aj aUd GdCdYGH GdUZjQI, aUd cQI GdjO, aUd GdUaGJ GdHOfjI hGdCOGA GdegGQj haUd GdeQMdI GdYeQjI hGdJj fMf HUOO OQGSJgG hgj eQMdI GdeQGgbI GdeHcQI, HYOgG hef CLd GdJMbb ef UMI GdaQVjGJ ef YOegG befG HGSJNOGe GdefgL GdJLQjHj dCfg GdefgL GdCfSH deKd gPg GdOQGSGJ eYJeOjf Ydi GdJUeje GdJLQjHj PGJ GNJHGQjf bHdj hHYOj Ydi YjfI hGMOI bOQJ H` (B15 (3dGYH GNJjQJ HGdWQjbI GdbUOjI hGdeeKdI dEMOi GdaQb GdeOQSjI dhdGjI JHSI hgh aQjb eJhSWI GdTgjO QGjS eMeO GdSYjO, HYOgG befG HJWHjb GdHQfGeL GdJOQjHj GdebJQM hGdPj GYJeOfG ajg Ydi GdCdYGH GdUZjQI HTcd QFjSj JQGhMJ eOJg (B03 (3CTgQ HeYOd (B03 (3MUU CSHhYjG Cj eG jYGOd (B36 (3MUI JOQjHjI JfhYJ GdCdYGH GdUZjQI GdeSJNOeI aj hMOGJgG MSH CgOGagG aefgG eG gh HOfj Ch egGQj Ch HOfj egGQj, hef CLd LeY GdHjGfGJ befG HGSJNOGe GdGNJHGQGJ GdHOfjI hGdegGQjI hgPG HYO GSJTGQI eLehYI ef GdNHQGA aj gPG GdeLGd, hdeYQaI eOi edGFeI gPg GdGNJHGQGJ befG HELQGA OQGSI GSJWdGYjI deYQaI GdCSS GdYedjI ddGNJHGQGJ eKd GdUOb hGdKHGJ, HYO LeY GdbjGSGJ GdbHdjI hGdHYOjI ddGNJHGQGJ GdQFjSI GdeSJNOeI aj GdOQGSI befG HELQGA GdOQGSI GdGMUGFjI hgPG bUO JMdjd GdHjGfGJ GdeJMUd YdjgG LQGA JWHjb GdGNJHGQGJ GdHOfjI hGdegGQjI ShGA GdGNJHGQ GdbHdj Ch GdHYOj hJQLeJgG GMUGFjG HGSJNOGe YOI CSGdjH GMUGFjI CHQRgG GNJHGQ (BT (3SJjhOfJ heYGed GdGQJHGW (BR (3HjQShf hHQfGeM GdMRe GdGMUGFjI (BSPSS(3, HYOG befG HYQV GdfJGFL hJMdjdgG hJaSjQgG hcPdc efGbTI GdaQVjGJ GdePchQI SGHbG hef Hjf Cge GdfJGFL GdeJhUd GdjgG aj gPg GdOQGSI eGjdj(B: (3GdeJGHYI JhUdfG Edi GdfJGFL GdJGdjI(B: 1- (3GdHQfGeL GdJOQjHj GdebJQM HGSJNOGe GdCdYGH GdUZjQI COi Gdi JfejI UaI GdbhI hGdJj JYJHQ ef Vef GdeJWdHGJ GdHOfjI GdCSGSjI ddGYHj cQI GdjO (B2- (3GdHQfGeL GdJOQjHj GdebJQM HGSJNOGe GdCdYGH GdUZjQI COi Gdi JfejI UaI GdSQYI hGdJj JYJHQ ef Vef GdeJWdHGJ GdHOfjI GdCSGSjI ddGYHj cQI GdjO (B3- (3GdHQfGeL GdJOQjHj GdebJQM HGSJNOGe GdCdYGH GdUZjQI COi Gdi JfejI UaI GdeOGheI hGdJj JYJHQ ef Vef GdeJWdHGJ GdHOfjI GdCSGSjI ddGYHj cQI GdjO (B4- (3GdHQfGeL GdJOQjHj GdebJQM HGSJNOGe GdCdYGH GdUZjQI COi Gdi JfejI UaI GdeQhfI hGdJj JYJHQ ef Vef GdeJWdHGJ GdHOfjI GdCSGSjI ddGYHj cQI GdjO (B5- (3GdHQfGeL GdJOQjHj GdebJQM HGSJNOGe GdCdYGH GdUZjQI COi Gdi JfejI UaI GdQTGbI hGdJj JYJHQ ef Vef GdeJWdHGJ GdHOfjI GdCSGSjI ddGYHj cQI GdjO (B6- (3GdHQfGeL GdJOQjHj GdebJQM HGSJNOGe GdCdYGH GdUZjQI CKQ GjLGHjG Ydi JfejI egGQI GdJeQjQ hGdGSJbHGd aj cQI GdjO hGdJj JYJHQ ef GdeJWdHGJ GdegGQjI GdeSJNOeI aj GdCOGA GdegGQj ddGYHj cQI GdjO (B7- (3GdHQfGeL GdJOQjHj GdebJQM HGSJNOGe GdCdYGH GdUZjQI CKQ GjLGHjG Ydi JfejI egGQI GdJfWjW aj cQI GdjO hGdJj JYJHQ ef GdeJWdHGJ GdegGQjI GdeSJNOeI aj GdCOGA GdegGQj ddGYHj cQI GdjO (B8- (3GdHQfGeL GdJOQjHj GdebJQM HGSJNOGe GdCdYGH GdUZjQI CKQ GjLGHjG Ydi JfejI egGQI GdJUhjH Hcd CfhGYg ef aj cQI GdjO hGdJj JYJHQ ef GdeJWdHGJ GdegGQjI GdeSJNOeI aj GdCOGA GdegGQj ddGYHj cQI GdjO (B9- (3GdHQfGeL GdJOQjHj GdebJQM HGSJNOGe GdCdYGH GdUZjQI CKQ GjLGHjG Ydi JfejI GdJMQcGJ GdgLhejI hGdOaGYjI aj cQI GdjO hGdJj JYJHQ ef GdeJWdHGJ GdegGQjI GdeSJNOeI aj GdCOGA GdegGQj ddGYHj cQI GdjO (B10- (3Gf GdHQfGeL GdJOQjHj GdebJQM HGSJNOGe GdCdYGH GdUZjQI CcKQ JaGYdG hbHhdG dOj dGYHj cQI GdjO CTHGd eeG COi Gdi OGaYjI GddGYHjf Gdi GdJOQjH heeGQSI GdfTGW HGdMeGS hGdSQhQ (B11- (3GdJOQjH HGdCdYGH GdUZjQI ef Hjf WQb GdJOQjH aj GdGQJbGA hJfejI GdUaGJ GdHOfjI ddGYHj cQI GdjO (B12- (3GdJOQjH HGdCdYGH GdUZjQI ef Hjf WQb GdJOQjH aj GdGQJbGA hJfejI GdCOGA GdegGQj ddGYHj s
(3cQI GdjO (B13- (3JhLO YdGbI GQJHGWjI YcSjI VYjaI Hjf GdbhI GdGfaLGQjI ddQLdjf hegGQI GdJeQjQ (B14- (3JhLO YdGbI GQJHGWjI YcSjI Hjf UaI GdbhI GdGfaLGQjI hegGQI GdGSJbHGd (B15- (3JhLO YdGbI GQJHGWjI WQOjI eJhSWI Hjf UaI JMed GdbhI ddQLdjf hegGQI GdJUhjH HGdhKH YGdjG (B16- (3JhLO YdGbI GQJHGWjI WQOjI eJhSWI Hjf UaI JMed GdbhI ddQLdjf hegGQI GdJUhjH HYO GdNOGY (B17- (3JhLO YdGbI GQJHGWjI YcSjI VYjaI Hjf UaI GdSQYI hegGQI GdJMQcGJ GdgLhejI hGdOaGYjI (B18- (3JhLO YdGbI GQJHGWjI YcSjI VYjaI Hjf UaI GdSQYI GdGfJbGdjI hegGQI GdJMQcGJ GdgLhejI hGdOaGYjI (B19- (3Ydi GdYehe gfGc YdGbI GQJHGWjI ShGA YcSjI Ch WQOjI Hjf GdUaGJ GdHOfjI hGdCOGA GdegGQj GYJeGOG Ydi GdHjGfGJ hGdeYdheGJ GdJj Jecf GdHGMK ef GdJhUd EdjgG hGdGSJQTGO HgG hHGdGSJfJGLGJ, haj VhA MOhO fJGFL GdHMK jhUj HeGjdj(B: 1- (3GSJYeGd GdCdYGH GdUZjQI aj HQGeL GdJOQjH dJfejI GdUaGJ GdHOfjI aj cQI GdjO (B2- (3GSJYeGd GdCdYGH GdUZjQI aj HQGeL GdJOQjH dJfejI GdCOGA GdegGQj aj cQI GdjO (B3- (3GSJNOGe GdfJGFL GdeJhUd GdjgG aj gPG GdHMK cbGYOI dELQGA OQGSGJ hHMhK GNQi (B4- (3GdGgJeGe HHQGeL GdJOQjH heMJhjGJgG hechfGJgG hELQGA GdHMK Ydi GdeQGMd GdSfjI GdCNQi (B5- (3ELQGA GdeRjO ef GdOQGSGJ hGdHMhK Ydi GSJNOGe GdCdYGH GdUZjQI Ydi HYV GdeJZjQGJ GdNWWjI hGdfaSjI hGdPgfjI aj GdeQGMd GdSfjI GdeNJdaI (B6- (3GOQGL hSGFd JOQjHjI CNQi Vef HQGeL GdJOQjH dJfejI GdeSJhi GdHOfj ddGYHjf (B7- (3GOQGL hSGFd JOQjHjI CNQi Vef HQGeL GdJOQjH dJfejI GdeSJhi hGdegGQj ddGYHjf (B8- (3GOQGL hSGFd JOQjHjI CNQi Vef HQGeL GdJOQjH dJfejI GdeSJhi GdNWWj ddGYHjf (B9- (3GOQGL hSGFd JOQjHjI CNQi Vef HQGeL GdJOQjH dJfejI GdeSJhi GdPgfj ddGYHjf (B10- (3GdJCcjO Ydi JWhjQ GdUaGJ GdHOfjI hGdJj dgG YdGbI eHGTQI eY GdegGQGJ GdGSGSjI aj cQI GdjO eKd egGQI GdJeQjQ hGdGSJbHGd hGdJUhjH (B11- (3HUaI YGeI jLH Ydi GdeYfjjf GdGgJeGe CcKQ HeLGd GdJOQjH hechfGJg heMJhjGJg hgPG dEYOGO aQO GYOGOG HOfjG hegGQjG hNWWjG hfaSjG s
(3OcJhQGIs
Keywords: (3GdGOGA GdegGQjs; (3GdGdYGH GdUZjQIs; (3GdUaGJ GdHOfjIs; (3cQI GdjOs; (3fXQjI h efgLjI GdJQHI GdHOfjI h GdQjGVjIs